Hydrologic sciences on the edge: the revolution in sensing and strategies - abstract - Tyler, Scott W., author; Colorado State University, publisher (Colorado State University. Libraries, 2015)
Abstract of award lecture "Hydrologic sciences on the edge: the revolution in sensing and strategies" given on March 24, 2015 by Scott W. Tyler, winner of the 2015 Hydrology Days Award.
Hydrology days 2015
AGU hydrology days 2015
2015 annual AGU hydrology days was held at Colorado State University on March 23 - March 25, 2015.
Keywords: Hydrology -- Congresses; Award winners